Unsinkable - Korman, Gordon. (Korman, Gordon. Titanic ;, 2011)
"The Titanic is meant to be unsinkable, but as it begins its maiden voyage, there's plenty of danger waiting for four of its young passengers. Paddy is a stowaway, escaping a deadly past. Sophie's mother is delivered to the ship by police - after she and Sophie have been arrested. Juliana's father is an eccentric whose riches can barely hide his madness. And Alfie is hiding a secret that could get him kicked off the ship immediately. The lives of these four passengers will be forever linked with the fate of the Titanic. And the farther they get from shore, the more the danger looms." (publisher).